Software agents for personalized training of collaborative e-learning teachers - Santana Mansilla, Pablo (2014)
In Computer Supported Collaborative Learning (CSCL) environments it is not enough to organize students in groups because interactions that originate the collaborative creation of knowledge do not happen spontaneously. Consequently, it is essential that e-tutors (teachers) promote interactions between students and coordinate discussions. To ease the workload (both temporal and cognitive) that supposes for teachers the coordination of discussions, software applications that give information about critical events of the interaction process have been developed so that teachers can intervene when group conflicts take place. Most e-tutors lack of experience with techniques of CSCL, but coordination skills of CSCL interactions belong to acquired skills category, it means this kind of skills can be developed through training processes. (Párrafo extraído del texto a modo de resumen)